2022
DOI: 10.1371/journal.pgen.1009943
|View full text |Cite
|
Sign up to set email alerts
|

Reassembling a cannon in the DNA defense arsenal: Genetics of StySA, a BREX phage exclusion system in Salmonella lab strains

Abstract: Understanding mechanisms that shape horizontal exchange in prokaryotes is a key problem in biology. A major limit on DNA entry is imposed by restriction-modification (RM) processes that depend on the pattern of DNA modification at host-specified sites. In classical RM, endonucleolytic DNA cleavage follows detection of unprotected sites on entering DNA. Recent investigation has uncovered BREX (BacteRiophage EXclusion) systems. These RM-like activities employ host protection by DNA modification, but immediate re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…The mechanism by which type 1 BREX systems restrict phage is not yet understood but occurs at a step prior to phage replication and does not involve cleavage of the phage genome ( 12 ). BREX systems presumably employ a DNA scanning mechanism that differentiates methylated (host) from unmethylated (foreign) sites; consistent with this, the Salmonella enterica BREX system (StySA) is observed to much more effectively restrict phage containing a higher number of unmodified PglX recognition sequences ( 21 ). Furthermore, given that all six or seven conserved genes in various type I BREX systems so far characterized, including BrxL, are required for restriction, it seems likely that a multi-protein BREX complex carries out this scanning function.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The mechanism by which type 1 BREX systems restrict phage is not yet understood but occurs at a step prior to phage replication and does not involve cleavage of the phage genome ( 12 ). BREX systems presumably employ a DNA scanning mechanism that differentiates methylated (host) from unmethylated (foreign) sites; consistent with this, the Salmonella enterica BREX system (StySA) is observed to much more effectively restrict phage containing a higher number of unmodified PglX recognition sequences ( 21 ). Furthermore, given that all six or seven conserved genes in various type I BREX systems so far characterized, including BrxL, are required for restriction, it seems likely that a multi-protein BREX complex carries out this scanning function.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, given that all six or seven conserved genes in various type I BREX systems so far characterized, including BrxL, are required for restriction, it seems likely that a multi-protein BREX complex carries out this scanning function. In the StySA BREX system, the authors identified a BrxC mutant containing a handful of relatively conserved mutations in its C-terminal domain that is competent for methylation but deficient for restriction ( 21 ). They proposed that BrxC’s C-terminal domain is critical for scanning and identifying unmethylated target sites and perhaps for licensing BrxL for phage restriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 C). Specifically, BrxA from E. fergusonii ATCC 35469 pEFER ( Picton et al., 2021 , 2022 ), E. coli HS2 ( Gordeeva et al., 2019 ; Isaev et al., 2020 ), Salmonella LT2 ( Zaworski et al., 2022 ), M. magneticum AMB-1, Acinetobacter NEB394 ( Luyten et al., 2022 ), Bacillus cereus H3081.97 ( Goldfarb et al., 2015 ), and Lactobacillus casei Zhang ( Hui et al., 2019 , 2022 ). All are annotated as domain of unknown function (DUF) 1819 proteins.…”
Section: Resultsmentioning
confidence: 99%